Ultra-small Pd nanoparticles derived from a supramolecular assembly for enhanced electrochemical reduction of CO2 to CO. Issue 66 (30th July 2019) - Chen, Ruru; Cao, Minna; Yang, Weiguang; Wang, Huimin; Zhang, Suyuan; Li, Hongfang; Cao, Rong
Abstract : Well-dispersed palladium nanoparticles based on a supramolecular assembly exhibit high selectivity, activity and stability for the conversion of CO2 to CO. Abstract : Ultra-small Pd nanoparticles were successfully prepared through reduction of a supramolecular assembly formed between the macrocyclic decamethylcucurbit[5]uril (Me10 CB[5]) and [PdCl4 ] 2− anions via H-bonds. The final Pd NPs exhibit excellent activity and stability toward the electrochemical reduction of CO2 to CO. This work provides a new strategy for the preparation of nanocatalysts.